2014
DOI: 10.1039/c3an02059b
|View full text |Cite
|
Sign up to set email alerts
|

A lateral flow assay for identification of Escherichia coli by ribosomal RNA hybridisation

Abstract: Existing technologies for analysis of microbiological contaminants in food or clinical samples are often expensive and require laboratory settings and trained personnel. Here we present a lateral flow assay employing gold nanoparticle-oligodeoxynucleotide conjugates and four-component sandwich hybridisation for direct detection of specific sequences in bacterial 16S ribosomal RNA. Combined with rapid "one step" lysis the developed procedure allows detection of 5 × 10(4) colony forming units per mL Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Lateral flow immunoassays (LFIA) offer an easy solution to these limitations as they are a simple, rapid and user friendly technique, that do not require time-consuming instrumental methods or technical expertise, allowing a low-cost point-of-care alternative (Chan et al, 2013;Pöhlmann et al, 2014;Li et al, 2015;Singh et al, 2015). Although LFIA is a well-recognized technique, a specific serological biomarker for PcP diagnosis has not been established (Morris and Masur, 2011;Esteves et al, 2015;Matos and Esteves, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lateral flow immunoassays (LFIA) offer an easy solution to these limitations as they are a simple, rapid and user friendly technique, that do not require time-consuming instrumental methods or technical expertise, allowing a low-cost point-of-care alternative (Chan et al, 2013;Pöhlmann et al, 2014;Li et al, 2015;Singh et al, 2015). Although LFIA is a well-recognized technique, a specific serological biomarker for PcP diagnosis has not been established (Morris and Masur, 2011;Esteves et al, 2015;Matos and Esteves, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The detection limit reported in this study which is 1 pg of genomic DNA is lower than that of a LAMP-NALFIA reported by Nimitphak et al (2008) (1 ng), a PCR-NALFIA by Blazkova et al (2009) (50 pg) and a LAMP-NALFIA by Kaewphinit et al (2013) (5 pg) whereas a PCR-NALFIA developed by Soo et al (2006) reported a similar LOD of 10 CFU/ml. An amplification-free NALFIA assay described by Pohlmann et al (2014) reported a higher detection limit of 10 4 CFU/ml.…”
Section: Optimisation Of Dry-reagent-based Late-pcr-nalf Assaymentioning
confidence: 99%
“…Alternatively, lateral-flow strip assays (LFSA), which are also based on antigen-antibody interactions, have been proven to be rapid (15-30 min) and relatively cheap; unfortunately, their lack of sensitivity and proneness to generating false-negative results in individuals infected with low concentrations of bacteria or viruses have limited their widespread adoption in the diagnostic clinic. [10][11][12] Alternatively, polymerase chain reaction (PCR) is also widely used for pathogen detection nowadays since nucleic acid sequences specific to a wide variety of microbes can be exponentially amplified to detectable levels in only two hours or less. Furthermore, the PCR assays are generally highly sensitive as well.…”
Section: Introductionmentioning
confidence: 99%